Outage Management and House of Quality to Improve Power Station Performance - Rochmansyah, Wahyu; Suef, Mokh. (Institut Teknologi Sepuluh Nopember, 2019)
The Coal Power Plant from Fast Tracking Project (FTP) owned by PT ABC is built by contractors from China. PT ABC is a company working in the area of the provision of electricity services business . In 2010 PT ABC establish business units new special serving the implementation of the operation & maintenance unit whenever the business units services operation & maintenance . Currently has been implement operation & maintenance four units of steam power plants a large scale with, namely Coal Fired Power Plant Indramayu , Coal-Fired Power Plant Rembang , Coal Fired Power Plant Pacitan And Paiton New Coal Fired Power Plant, The condition of generating equipment is not good enough. Maintenance undertaken is currently inadequate again despite the condition of the equipment age is still young. The maintenance of the power plant is needed so that the power plant can improve the quality of service in order to meet the community's guidance and the challenges of technological development. To improve overhaul planning and preparedness at an optimum level, maintenance management is required using Outage Management, which is a synergistic and sustainable process of Planning, Monitoring, Controlling and Evaluation of Planed Outage and using House of Quality (HOQ). Outage Management is used to optimize power plant maintenance activities by applying the rules of Right Problem, Right Solution, Right Design, Right Implementation. By using House of Quality (HOQ), broadly voice of costumer attempted to be converted directly into technical characteristics of maintenance. By applying it is expected the company will be able to achieve technical characteristics in accordance with the target set. from attribute of quizoner made there is Priority Voice of customer (VOC) requirement to Critical Customer Requirements (CCR) are Safety Base Outage Management on Frame Outage Management on priority 1 with score 97 while Outage Management on score 72